Potassium fertilization as salt stress attenuator in sour passion fruit - Weslley Bruno Belo de Souza; Geovani Soares de Lima; Francisco Jean da Silva Paiva; Lauriane Almeida dos Anjos Soares; Reynaldo Teodoro de Fátima; André Alisson Rodrigues da Silva; Hans Raj Gheyi; Pedro Dantas Fernandes (Ciência Rural, 2023)
ABSTRACT: Water scarcity associated with irregular rainfall in the semi-arid region of Northeastern Brazil stands out as a limiting factor for agricultural production. Thus, the use of waters with high concentration of salts is an alternative to expand irrigated agriculture in this region. In this context, this study evaluated the water status, intercellular electrolyte leakage, photosynthetic pigments, and gas exchange of ‘BRS SC1’ sour passion fruit as a function of irrigation with water of different levels of salinity and potassium doses. The experiment was carried out in pots adapted as drainage lysimeters under field conditions at the Experimental Farm of the Federal University of Campina Grande in São Domingos - PB, Brazil. The experimental design was randomized blocks, in a 5 × 4 factorial scheme, whose treatments were obtained by combining two factors: five levels of electrical conductivity of irrigation water - ECw (0.3, 1.1, 1.9, 2.7, and 3.5 dS m-1), associated with four potassium doses (60, 80, 100, and 120% of the recommendation), with three replicates. Water with electrical conductivity greater than 0.3 dS m-1 reduced the relative water content, chlorophyll a and chlorophyll b contents, CO2 assimilation rate, and instantaneous water use efficiency of ‘BRS SC1’ sour passion fruit plants. The estimated potassium dose of 85% of the recommendation (equivalent to 293 g per plant per year) mitigated the deleterious effects of salt stress on stomatal conductance, transpiration, internal CO2 concentration, and instantaneous carboxylation efficiency of passion fruit ‘BRS SC1’.